REALITAS SOSIAL DALAM NOVEL CEMBURU DI HATI PENJARA SUCI KARYA MA’MUN AFFANY (KAJIAN SOSIOLOGI SASTRA) - Lailin Naimah, Nur; Supratno, Haris; Kholifatu Amalia Shofiani, Arisni (Discovery, 2019)
Social reality is an event that occurs in community life. Basically humans as socialbeings, which means that humans in this world cannot live alone without otherpeople living their lives. In this study will explain some analysis of social reality thatis made by the characters in the novel subjectively. The purpose of the study will beto produce insights about the social reality in the form of novel literature. The socialreality obtained from the novel was later developed in the study of literary soology.In this study using a qualitative approach, while the qualitative descriptive method isused to describe the research data. Data collection uses the techniques of reading,giving signs, gathering and giving conclusions. Two data analysis techniques arecontent analysis and descriptive analysis. In using the approach, collecting andanalyzing the social reality contained in the novel will provide new knowledge that was initially not obtained. The results of this study are in social reality that there areexternalization, objectivation and internalization of the novel Ma'unun AffanyJealous at the Heart of the Holy Prison. These three points of social reality areelaborated in detail and are related to the current state of society. The existence ofthe translation has hope that the reader can easily understand the social reality that isobtained from the novel.Keywords: reality, social, and novel